Urban underlying surface modulates summertime thunderstorm processes and associated lightning activities - T. Shi; T. Shi; Y. Yang; G. Lu; Z. Zheng; Y. Zi; Y. Tian; L. Liu; S. Lolli (Atmospheric Chemistry and Physics)
The urban underlying surface may have a significant impact on thunderstorm processes and lightning activities, but there is still a lack of explanation of the mechanism. Through a comparative analysis of cloud-to-ground (CG) lightning location datasets in three cities of varying sizes in China, it was observed that for small cities, CG activities tend to cluster towards the city center, whereas in large cities, CG activities tend to accumulate in the city periphery. Radar echoes indicated the occurrence of a significant barrier effect as the thunderstorm that occurred on 13 July 2017 (“0713” case) passed over Beijing's built-up area. An analysis of ground observations revealed that when this thunderstorm passed over the rough urban underlying surface, a separation of the near-surface cold pool emerged. This separation led to the weakening of vertical airflow and the breakdown of the convergence line, ultimately triggering the bifurcation and movement of the thunderstorm. The Weather Research and Forecasting (WRF) numerical simulations have facilitated our further exploration into the potential mechanism of the barrier effect. When a portion of the built-up area was replaced with bare land, the separation of the cold pool and the breakdown of the convergence line were notably mitigated. Additionally, the building density could also influence the evolution of the cold pool and convergence line. Consequently, the urban underlying surface might be a potentially crucial factor affecting the thunderstorm processes and CG activities. Our findings provide crucial scientific insights for refined forecasting, early warning, and risk assessment of lightning disasters, strategy formulation for urban disaster prevention and mitigation, and resilient city planning and development.